AB1272 Subacromial steroid injection do not increase the rate of full-thickness rotator cuff tear. (23rd January 2014) - Ramírez, J.; Pomés, I.; Cabrera, S.; Gόmez, M.E.; Inciarte, J.; Rosario, V.; Pomés, J.; Sanmartí, R.; Cañete, J.
Abstract : Background: Up to 35% of patients with shoulder pain have a full-thickness rotator cuff tear. It has been proven a deleterious effect of corticosteroid on collagen. However, the influence of corticosteroid injection in the incidence of rotator cuff tears is unknown. Objectives: The aim of this study was to evaluate the risk of corticosteroid injection in the incidence of full-thickness rotator cuff tear. Secondary outcomes were the incidence of full-thickness rotator cuff tear between patients with partial-thickness rotator cuff tear and the improvement in shoulder pain and function. Methods: Prospective, open-label study. Patients with unilateral painful shoulder without previous local steroid injection were recluted. Clinical and ultrasound assessment were practiced in the first (day 0) and the last visit (day 90). Patients with full-thickness rotator cuff tear were excluded. Patients received a standard subacromial infiltration of 1 cc of triamcinolona depot. 1cc of mepivacaina was injected in 7 patients for clinical decision (mainly poorly controlled diabetes). A radiologist and a rheumatologist experienced in musculoeskeletical ultrasound performed the ultrasound scans and clinical examination, respectively, of shoulder pain. Results: 89 patients with shoulder pain were evaluated. 47 (52.8%) had full-thickness rotator cuff tear in the first visit and were excluded. 42 patients completed the study (29 women and 13 men, the mean age of patients was 61.1 years-old). 35 received an injection of 1 cc of triamcinolone depot and 7 were infiltrated with mepivacaine (2 patients for steroid allergy and 5 patients with poorly controlled diabetes). At the end of the study, 7 full-thickness rotator cuff tears were found. 1/7 (14.2%) in the mepivacaine group and 6/35 (17.1%) in the triamcinolone depot group. Among 18 patients who had a partial-thickness rotator cuff tear in the first visit, 6 suffered a complete tear of the rotator cuff after 3 months (1/4 in the mepivacaine group and 5/14 in the triamcinolone depot group). 4/7 patients (57.1%) had a great improvement in shoulder pain (more than 80% in VAS score) in the mepivacaine group, while 14/35 (40%) had it in the triamcinolone depot group. Only one patient worsened the symptoms, because of a new full-thickness rotator cuff tear. 39 patients (92.8%) recovered the normal range of movement after 3 months. Conclusions: Subacromial steroid injection did not increase the rate of full-thickness rotator cuff tear expected in a population with shoulder pain. More than half patients with shoulder pain have a full-thickness rotator cuff tear in the first visit. Disclosure of Interest: None Declared